Improvement of sludge electrodewatering by anode flushing. Issue 3 (17th February 2016) - Citeau, Morgane; Loginov, Maksym; Vorobiev, Eugene
ABSTRACT: An improvement of the sludge electrodewatering process is proposed: anode flushing by filtrate recirculation. According to this technique, the mixture of filtrates obtained at cathode and anode sides is used for continuous flushing of the anode chamber of the filter press during electrodewatering. Anode flushing aims to eliminate essential problems of electrodewatering: ohmic heating, rise of electric energy consumption, electrode corrosion, and filtrate contamination. This is attained by better control of the filtrate pH, the filter cake temperature, and the dryness at the anode side, where the physicochemical conditions are most aggressive. The efficiency of the proposed technique is evaluated at lab scale on drilling sludge electrodewatering with and without anode flushing. In experiments without anode flushing, increasing electric current density caused strong increase of anode temperature, desiccation of the filter cake at the anode side, rise of voltage, and significant alkaline contamination of filtrate. The application of anode flushing allowed controlling the electric field strength and temperature. Thus, the dewatering of the sludge has been extended at high electric field without damaging the filter equipment by drastic heating. Furthermore, it reduced filtrate contamination by neutralization of the electrolysis products.